Willingness to pay for cataract surgeries among patients visiting eye care facilities in Dhaka, Bangladesh - Islam, Muhammed Nazmul; Engels, Thomas; Hossain, Shafayet; Sarker, Malabika; Rabbani, Atonu (Applied health economics and health policy, 2019)
BackgroundCataract is the leading cause of avoidable blindness globally. It is estimated that 89% of people with visual impairment live in low- and middle-income countries where the cost of cataract surgery represents a major barrier for accessing these services. Developing self-sustaining healthcare programs to cater the unmet demands warrants a better understanding of patients’ willingness to pay (WTP) for their services.ObjectivesUsing a sample of patients visiting eye care facilities in Dhaka, Bangladesh, we estimate WTP for two different cataract extraction techniques, namely small incision cataract surgery (SICS) and phacoemulsification.MethodsWe used contingent valuation (CV) approach and elicited WTP through double-bounded dichotomous choice experiments. We interviewed 556 randomly selected patients (283 for SICS and 273 for phacoemulsification) from five different eye care hospitals of Dhaka. In this paper, we estimated the mean and marginal WTP using interval regression models. We also compared the estimated WTP and stated demand for cataract surgeries against the prevailing market prices of SICS and phacoemulsification.ResultsWe found the mean WTP of BDT 7579 (US$93) for SICS and BDT 10,208 (US$126) for phacoemulsification are equivalent to 12 and 16 days of household income, respectively. Household income and assets appeared as the major determinants of WTP for cataract surgeries. However, we did not find any significant association with gender, occupation, and household size among other socioeconomic characteristics. Comparisons between market prices and average WTP suggest it is possible to have a viable market for SICS, but a subsidy-based model for phacoemulsification will be financially challenging because of low WTP and high costs.ConclusionOur findings suggest lower-cost SICS can potentially provide patients access to surgeries to treat cataract conditions. Moreover, price discrimination and cross-subsidization could be a viable strategy to increase the service-uptake as well as ensure financial sustainability.